Preparation of cassava starch grafted with polystyrene by suspension polymerization - Kaewtatip, K.; Tanrattanakul, V.
Cassava starch grafted with polystyrene (PS-g-starch)copolymer was synthesized via free-radical polymerization of styrene by using suspension polymerization technique. Potassium persulfate (PPS)was used as an initiator and water was used as a medium. The graft copolymer was characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, thermal gravimetric analysis, X-ray diffraction and scanning electron microscopy. The sub-micron spherical beads of PS were observed on the surface of starch granules. SEM micrographs showed porous patches of PS adhering on the starch granules after Soxhlet extraction. FTIR spectra also indicated the presence of PS-g-starch copolymer. XRD analysis exhibited insignificant changes in crystalline structure and degree of crystallinity. The effects of starch:styrene weight ratio, amount of PPS, reaction time and reaction temperature on the percentage of grafting - G (
Keywords: CASSAVA STARCH; POLYSTYRENE; BIODEGRADABLE POLYMER; GRAFT COPOLYMER; BIOPLASTIC